Melittopalynology and Trophic niche analysis of Apis cerana and Apis mellifera in Yunnan Province of Southwest China - Yu-Jia Liu; Tian-Rui Zhao; Xue-Wen Zhang; Cheng Liang; Feng-Yun Zhao (Sociobiology)
The present study reports results of qualitative melittopalynological analyses of 34 honey samples of Apis cerana and Apis mellifera between 2011 and 2012 in Mengzi (China Yunnan) and the trophic niche analysis of two bee species on pollen food resources. A diverse spectrum of 17 pollen types from 14 families was identified with the Asteraceae and Myrtaceae being most frequent at non-nectar flow and the Lythraceae being most frequent at main nectar flow of pomegranate. The results of trophic niche analysis to Apis cerana and Apis mellifera are these, at non-nectar flow, the Niche breadth are 0.65 and 0.57, respectively; at nectar flow, the values are 0.41 and 0.24, respectively. Trophic niche overlap index, the value of nectar flow(0.68) is greater than non-nectar flow(0.61). Interspecific competition index, the value of nectar flow(0.92) is also greater than non-nectar flow(0.77). These results may promote the development of local beekeeping and help scholars assessing the impact of introduced bees on native bees in China.